2013
DOI: 10.1111/joim.12104
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of Concern: HMGB1 mediates splenomegaly and expansion of splenic CD11b+ Ly‐6Chigh inflammatory monocytes in murine sepsis survivors

Abstract: BackgroundMore than 500,000 hospitalized patients survive severe sepsis annually in the USA. Recent epidemiological evidence, however, demonstrated that these survivors have significant morbidity and mortality, with 3-year fatality rates higher than 70%. To investigate the mechanisms underlying persistent functional impairment in sepsis survivors, here we developed a model to study severe sepsis survivors following cecal ligation and puncture (CLP).MethodsSepsis was induced in mice by CLP and survivors were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 29 publications
7
46
0
Order By: Relevance
“…Therefore, because of high levels of HMGB1 locally, the dose of mAb 2G7 used here may have been insufficient to neutralize HMGB1 completely. Although we cannot exclude this possibility, previous studies in BXSB lupus mice and a sepsis model have clearly shown a positive effect of anti-HMGB1 antibody treatment, despite the development of splenomegaly (21,36).…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Therefore, because of high levels of HMGB1 locally, the dose of mAb 2G7 used here may have been insufficient to neutralize HMGB1 completely. Although we cannot exclude this possibility, previous studies in BXSB lupus mice and a sepsis model have clearly shown a positive effect of anti-HMGB1 antibody treatment, despite the development of splenomegaly (21,36).…”
mentioning
confidence: 83%
“…This antibody has been extensively characterized previously with respect to its HMGB1 neutralizing activity in in vitro and in vivo studies. The neutralizing activity of anti-HMGB1 monoclonal antibody (mAb) has been tested in cell culture assays, with both human and mouse macrophages, and in animal models of HMGB1-mediated damage, such as sepsis (8,(19)(20)(21)(22)(23)(24). Moreover, anti-HMGB1 mAb 2G7 has been shown to neutralize the cytokine isoform of HMGB1 (19).…”
Section: Neutralizing Anti-hmgb1 Antibodymentioning
confidence: 99%
“…Disulfide HMGB1 binds to the cell sur face receptor complex MD2TLR4 (12) to enhance release of TNF and IL6, cytokines that have been implicated in the onset of anemia of inflammation in sepsis and negatively regulate erythro poiesis (13,14). We recently identified HMGB1 as a mediator of persistent mor bidity and mortality in sepsis survivors (15,16). Here we show that HMGB1 is both necessary and sufficient to induce anemia in murine sepsis survivors and that HMGB1 is a therapeutic target.…”
Section: Complete Blood Countsmentioning
confidence: 99%
“…The mono clonal antibody detects an epitope in sequence 46-63 of the box A domain, more specifically around glycine in position 58, since this is the single discriminating residue between HMGB1 and HMGB2 in this sequence. On d 9-11 after surgery, CLP survivors received intraperitoneal injections of either antiHMGB1 mono clonal antibody (50 μg/day in 200 μL PBS) or mouse IgG2b (ESMD Chemicals) as isotype control (15). Specificity of 2G7 has been previously demonstrated (15,16).…”
Section: Administration Of Anti-hmgb1 Neutralizing Monoclonal Antibodymentioning
confidence: 99%
See 1 more Smart Citation